2018
DOI: 10.1371/journal.pone.0193002
|View full text |Cite|
|
Sign up to set email alerts
|

Reward abundance interferes with error-based learning in a visuomotor adaptation task

Abstract: The brain rapidly adapts reaching movements to changing circumstances by using visual feedback about errors. Providing reward in addition to error feedback facilitates the adaptation but the underlying mechanism is unknown. Here, we investigate whether the proportion of trials rewarded (the ‘reward abundance’) influences how much participants adapt to their errors. We used a 3D multi-target pointing task in which reward alone is insufficient for motor adaptation. Participants (N = 423) performed the pointing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 32 publications
4
40
0
Order By: Relevance
“…Using a weight-shifting task, we replicated a finding from studies using arm movements: increased variability following non-rewarded trials as compared to rewarded trials [4,5,[8][9][10][11][12][13]. In addition, we found a ratio between variability due to exploration and sensorimotor noise of 0.78.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Using a weight-shifting task, we replicated a finding from studies using arm movements: increased variability following non-rewarded trials as compared to rewarded trials [4,5,[8][9][10][11][12][13]. In addition, we found a ratio between variability due to exploration and sensorimotor noise of 0.78.…”
Section: Discussionsupporting
confidence: 79%
“…Therefore, this finding implies that studying sensorimotor noise and exploration requires a high number of trials. In the literature, human motor learning experiments usually seem to contain up to 200 feedback trials [8,10,12,[31][32][33][34][35][36], although some studies report higher numbers, up to 900 trials [4,5,11,16,19,37,38]. An example of a study incorporating many trials is [14], in which rats performed 300k trials on average.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This pattern of behavior is consistent with a win-stay, lose shift strategy 34,35 . Notably, it has been shown that reward is not effective in shaping motor behaviors unless participants are aware of the manipulation being rewarded or if reward is too abundant 36,37 , probably due to participants not engaging in exploratory behaviors. Future work may also consider the psychological implications of reward and punishment given during learning, and how this interacts with behavioral variability and cognitive strategies.…”
Section: Engaging Alternative Cognitive Strategiesmentioning
confidence: 99%